2014
DOI: 10.4293/jsls.2014.00128
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ovulation Induction Protocols After Endometrioma Resection

Abstract: Background and Objectives:The aim of this study was to compare the in vitro fertilization (IVF) outcomes of long gonadotropin-releasing hormone agonist (GnRH-a) and GnRH-antagonist (GnRH-ant) protocols in endometriosis patients who have undergone laparoscopic endometrioma resection surgery. To our knowledge, there is no study in the current literature that compares the effectiveness of long GnRH-a and GnRH-ant protocols in management of IVF cycles in endometriosis patients who underwent laparoscopic endometrio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 41 publications
4
29
0
Order By: Relevance
“…Many researchers have attempted to overcome this obstacle using either oral contraceptive pills [18] or levonorgestrel-releasing IUDs [19], but these methods cannot directly facilitate IVF. Two retrospective studies reported that GnRH antagonist (GnRH-ant) protocols can achieve comparable results to those of long-term GnRH-a protocols in EMs patients [20,21]. However, a Cochrane meta-analysis by Al-Inany and Aboulghar suggested that GnRH-ant protocols negatively affected pregnancy rates [22].…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have attempted to overcome this obstacle using either oral contraceptive pills [18] or levonorgestrel-releasing IUDs [19], but these methods cannot directly facilitate IVF. Two retrospective studies reported that GnRH antagonist (GnRH-ant) protocols can achieve comparable results to those of long-term GnRH-a protocols in EMs patients [20,21]. However, a Cochrane meta-analysis by Al-Inany and Aboulghar suggested that GnRH-ant protocols negatively affected pregnancy rates [22].…”
Section: Discussionmentioning
confidence: 99%
“…The two protocols, GnRH-a and GnRH-ant, were used for endometriosis patients undergoing COS. Pabuccu et al, in their prospective randomized trial study compared the long GnRH-a protocol to the GnRH-ant in endometriosis (grade I and II) and endometrioma in ICSI cycles, and reported that both protocols are equally effective in such patients (41). In a recent study, Bastu et al showed that the outcomes of IVF in both protocols were similar in endometriosis patients (42).…”
Section: Discussionmentioning
confidence: 99%
“…this combination of strategy of coh is proven by many studies to improve clinical pregnancy rate, ongoing pregnancy rate, and implantation rate. [17][18][19][20] the duration of downregulation also affects the pregnancy outcome. early studies also revealed that 3-6 months duration of downregulation might improve the overall success rate of ivF.…”
Section: Discussionmentioning
confidence: 99%
“…however, the efficacy needs to be balanced with the cost and side effects of hypo-estrogenism to the women. [17][18][19] the integrated approach of surgery-ivF-et yield a good pregnancy rate of 56% compared to 37% if surgery alone. 21,22 our study also demonstrated that the combination of surgery with integrated stimulation (Gnrh analogue + coh)-icSi-et also enhances the pregnancy outcome in endometriosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation